THE PERCEPTION OF BUSINESS ENGLISH COMMUNICATION 2020 STUDENTS TOWARD THE USE OF YOUTUBE VIDEOS TO IMPROVE SPEAKING SKILL - Rezky, Nur; Luhriyani, Seny; Hajar, Andi (Universitas Negeri Makassar, 2023)
This study is the perception research that aimed to find out students' perceptions regarding the use of YouTube videos to improve speaking skills and to find out whether YouTube videos can be used to improve students' speaking skills. This study used a quantitative method by taking samples with a questionnaire research instrument. The subjects of this study were 30 Business English Communication Students Class of 2020. Data analysis used in this study is data analysis using validity and reliability tests. The results showed that the perceptions of students indicated that using YouTube videos to improve speaking skills was effective. And the results of the questionnaire consisting of 19 items show the results obtained from the study, namely 78% in the Strongly Agree category. Based on these results, YouTube videos can be productive and effective media to be used as learning media to improve speaking skills which also include student vocabulary and pronunciation.